The effectiveness of short-term intensive psychodynamic therapy on emotional self-awareness, empathy and self-compassion in psychotherapy trainees - Aminifar, Salma; Bahrami Hidaji, Maryam; Kraskian Mujembari, Adis; Mansoobifar, Mohsen; Peyvandi, Parisa (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Paying attention to the mental state of psychotherapy trainees plays an essential role in preparing students to enter the field of therapy. Therefore, this research was conducted with the aim of determining the effectiveness of short-term intensive psychodynamic therapy on emotional self-awareness, empathy and self-compassion in psychotherapy trainees. Methods: It was a semi-experimental research with a pre-test-post-test design with two experimental and control groups and a two-month follow-up. The statistical population of the research consisted of all the psychotherapist trainees in Tehran in 2021, who were selected by the available sampling method, 30 people and randomly replaced in two groups of 15 people. Data collection was done with emotional self-awareness questionnaire (Rifi et al., 2008), empathy questionnaire (Mehrabian and Epstein, 1972) and self-compassion questionnaire (Neff, 2003). For each of the experimental groups, an intervention program was held in the form of weekly meetings. In addition to descriptive statistics, data analysis was performed with mixed analysis of variance and Bonferroni's post hoc test. Results: The results showed that in the post-test period, between the mean scores of emotional self-awareness (p